An organic sludge conditioner, its preparation method and application

CN121063799BActive Publication Date: 2026-10-09HYDROCARBON (SUZHOU) ENVIRONMENTAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511273205.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-08
Publication Date
2026-10-09
Estimated Expiration
2045-09-08

AI Technical Summary

Technical Problem

1、投加量大,处理成本高:PAC的有效投加量通常为污泥干重的2%-8%,大量药剂消耗导致处理成本居高不下,尤其对于大规模污泥处理场景经济性较差

Benefits of technology

(1)本发明通过采用阳离子改性淀粉、木质素磺酸钠接枝丙烯酰胺共聚物、纳米级生物质炭、壳聚糖季铵盐和复合酶制剂组成的有机复合体系作为污泥调理剂,替代传统无机PAC,使得调理剂完全摒弃金属盐成分,从根本上避免了无机成分引入导致的污泥量增加和二次污染风险;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to sludge conditioning technical field, disclose a kind of organic sludge conditioner and its preparation method and application, comprising: 40-60 parts cationic modified starch, 20-30 parts sodium lignosulfonate graft acrylamide copolymer, 10-20 parts nanoscale biomass charcoal, 5-10 parts chitosan quaternary ammonium salt and 1-3 parts composite enzyme preparation.The organic sludge conditioner of the present application is organic composite system instead of traditional inorganic PAC, completely abandon metal salt component, fundamentally avoid the sludge quantity increase and secondary pollution risk caused by inorganic component introduction;While the organic sludge conditioner of the present application has obvious conditioning effect: effective dosage is reduced to 0.15%-0.6% of sludge dry weight, only 1 / 13-1 / 11 of traditional PAC dosage, sludge quantity is reduced by 13%-17% compared with PAC conditioning, sludge heat value is increased to 18-22MJ / kg after conditioning, increased by 15%-25% compared with PAC conditioning sludge.Moreover, the present application can also be applied to the treatment of sewage containing silicon, can improve sludge characteristics, remove part of oil stain in sewage, prevent filter cloth from being blocked, improve the quality of recycled water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sludge conditioning technology, and more specifically, to an organic sludge conditioner, its preparation method, and its application. Background Technology

[0002] With the acceleration of urbanization and the expansion of industrial production, the amount of sludge generated by municipal wastewater treatment plants and industrial enterprises has increased dramatically. Sludge, as a complex colloidal system, contains a large amount of water (typically above 95%), and its dewatering treatment is a crucial step in reducing, rendering harmless, and recycling sludge. To improve sludge dewatering performance, conditioning agents are needed to disrupt the colloidal structure of the sludge and promote sludge-water separation. Among these methods, chemical conditioning is widely used due to its simplicity and high efficiency.

[0003] Currently, inorganic metal salts such as polyaluminum chloride (PAC), aluminum sulfate, and ferric chloride are commonly used as sludge conditioners in the industry. Among them, PAC has become the mainstream choice for conditioning municipal sludge and industrial organic sludge due to its low price and wide applicability. Its mechanism of action is mainly to neutralize the negative charge on the surface of sludge particles by releasing metal ions after dissolution, compressing the electric double layer, and forming flocs through the adsorption and bridging effect of hydrolysis products, thereby improving the sludge dewatering performance.

[0004] However, existing PAC conditioning techniques have the following significant drawbacks: 1. Large dosage and high treatment cost: The effective dosage of PAC is usually 2%-8% of the dry weight of sludge. The large amount of reagent consumption leads to high treatment costs, which is particularly uneconomical for large-scale sludge treatment scenarios.

[0005] 2. Increased sludge volume limits the reduction effect: As an inorganic metal salt, PAC introduces a large amount of inorganic components, resulting in a 10%-15% increase in sludge volume after filtration, which contradicts the treatment goal of sludge reduction and increases subsequent transportation and disposal costs.

[0006] 3. Reduced calorific value and low resource utilization rate of sludge: The inorganic components (such as aluminum salts) introduced by PAC will dilute the organic matter content in the sludge, reducing the calorific value of the sludge by 20%-30% (usually to below 14-16 MJ / kg), making it difficult to meet the calorific value requirements for resource utilization such as incineration power generation, thus limiting the energy conversion pathway of sludge.

[0007] 4. Potential secondary pollution risk: The aluminum ions remaining in the sludge after conditioning may enter the environment through landfill leachate or land application, posing a risk of heavy metal accumulation and failing to meet current stringent environmental protection standards.

[0008] Therefore, proposing an organic sludge conditioner has significant practical implications. Summary of the Invention

[0009] In view of this, the present invention proposes an organic sludge conditioner, its preparation method and application, aiming to solve at least one of the problems in the background art.

[0010] This invention provides an organic sludge conditioner, comprising the following components in parts by weight: 40-60 parts cationic modified starch, 20-30 parts sodium lignosulfonate grafted acrylamide copolymer, 10-20 parts nano-sized biochar, 5-10 parts chitosan quaternary ammonium salt, and 1-3 parts compound enzyme preparation.

[0011] Preferably, the cationic modified starch is obtained by the following method: Starch was added to water to prepare a 25% concentration suspension, stirred at 30°C for 30 minutes, and cellulase and amylase were added at a mass ratio of 1:1, wherein the mass of cellulase and amylase was 0.5% of the mass of starch. After enzymatic hydrolysis for 30 minutes, the temperature was raised to 80°C for 10 minutes to inactivate the enzymes. The pH of the enzymatically hydrolyzed suspension was adjusted to 8.5 by adding 10% sodium hydroxide solution and stirring for 15 min. Then, 10% sodium hydroxide solution was added to adjust the pH to 11.0. 3-chloro-2-hydroxypropyltrimethylammonium chloride (18% by weight of starch) was added for ultrasonic-assisted modification. After the modification was completed, the suspension was subjected to gradient cooling and then centrifuged to collect the precipitate. The precipitate was washed three times with 70% ethanol solution. The washed precipitate was dried at -40°C and under a vacuum of 0.1 MPa and then pulverized to obtain the cationic modified starch.

[0012] Preferably, the ultrasonic-assisted modification temperature is 65°C, the ultrasonic power is 300W, the ultrasonic frequency is 20kHz, and the reaction time is 1.5 hours.

[0013] Preferably, the gradient cooling specifically involves lowering the temperature of the modified suspension to 40°C, holding it at that temperature for 30 minutes, and then lowering it to 25°C and holding it at that temperature for 30 minutes.

[0014] Preferably, the sodium lignosulfonate-grafted acrylamide copolymer is obtained by the following method: Sodium lignosulfonate was dissolved in water to prepare an 8% (w / w) sodium lignosulfonate solution. 5% (w / w) of a 30% (w / w) hydrogen peroxide solution was added to the sodium lignosulfonate solution. After stirring at 50°C for 60 minutes, 30% (w / w) of acrylamide monomer and 0.2% (w / w) of sodium persulfate were added. The reaction was carried out under nitrogen protection at 45°C for 1 hour. After the reaction was completed, the temperature was raised to 60°C, and 0.3% (w / w) of sodium bisulfite was added to continue the reaction for 2 hours to obtain a polymer. The polymer was then post-treated to obtain the sodium lignosulfonate-grafted acrylamide copolymer.

[0015] Preferably, the post-processing specifically includes: The polymer was dialyzed with water as the dialysate for 48 hours, with the dialysate being changed every 8 hours. After the dialysate was dialyzed, the polymer was dried at -45°C and a vacuum of 0.1 MPa for 24 hours.

[0016] Preferably, the nanoscale biochar is obtained by the following method: After crushing rice husks, they were mixed with water at a mass ratio of 1:10. Phosphoric acid at a mass of 3% of the rice husks was added, and the mixture was subjected to a hydrothermal reaction at 180°C for 2 hours to obtain a carbon-rich precursor. The carbon-rich precursor was heated to 300°C at a rate of 5°C / min under a nitrogen atmosphere and held at that temperature for 1 hour. Then, it was heated to 550°C at a rate of 5°C / min while water vapor was continuously introduced at a flow rate of 0.5 L / h and held at that temperature for 1.5 hours. After that, it was naturally cooled to 100°C and then removed. It was then pulverized at a pulverizing pressure of 0.8 MPa and a rotation speed of 10,000 r / min to obtain the nanoscale biochar.

[0017] Preferably, the compound enzyme preparation consists of 50% cellulase, 30% protease and 20% lipase, and the enzyme activity in the compound enzyme preparation is ≥1000U / g.

[0018] This invention also proposes a method for preparing an organic sludge conditioner, comprising the following preparation steps: The cationic modified starch was mixed with chitosan quaternary ammonium salt and stirred at 30°C and 400 r / min for 10 minutes. Then the lignin graft copolymer was added, the temperature was raised to 50°C, the stirring speed was reduced to 200 r / min, and the mixture was stirred for 20 minutes. Then the nano-biochar was added, the temperature was raised to 60°C, and the mixture was stirred at 200 r / min for 15 minutes. Finally, the temperature was lowered to 25°C, the compound enzyme preparation was added, and the mixture was stirred at 100 r / min for 5 minutes to obtain the organic sludge conditioner.

[0019] This invention also proposes the application of an organic sludge conditioner in sludge conditioning.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention uses an organic composite system composed of cationic modified starch, sodium lignosulfonate grafted acrylamide copolymer, nano-scale biochar, chitosan quaternary ammonium salt and composite enzyme preparation as a sludge conditioner to replace the traditional inorganic PAC, so that the conditioner completely eliminates metal salt components, fundamentally avoiding the increase in sludge volume and the risk of secondary pollution caused by the introduction of inorganic components. (2) The present invention utilizes the biodegradation of sludge colloidal structure by compound enzyme preparations (cellulase, protease, lipase) and the charge neutralization effect of cationic modified starch and chitosan quaternary ammonium salt to form a synergistic effect, which significantly improves the efficiency of sludge floc formation and reduces the effective dosage to 0.15%-0.6% of the sludge dry weight, which is only 1 / 13-1 / 11 of the traditional PAC dosage, thus greatly reducing the treatment cost; (3) This invention achieves efficient adsorption bridging by grafting sodium lignosulfonate with acrylamide copolymer into a polymer chain structure, and constructs drainage channels by combining the porous structure of nano-biochar, thereby improving the sludge dewatering efficiency. Moreover, due to the absence of inorganic residues, the amount of sludge is reduced by 13%-17% compared to PAC conditioning, significantly enhancing the sludge reduction effect. (4) This invention utilizes the high calorific value characteristics (calorific value ≥25MJ / kg) of nano-biochar (rice husk base) and the retention effect of organic components on the organic matter of sludge, so that the calorific value of the conditioned sludge is increased to 18-22MJ / kg, which is 15%-25% higher than that of PAC-conditioned sludge, and fully meets the calorific value requirements for resource utilization such as incineration power generation. Detailed Implementation

[0021] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.

[0022] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included within this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0023] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0024] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0025] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0026] This invention provides an organic sludge conditioner, comprising the following components in parts by weight: 40-60 parts cationic modified starch, 20-30 parts sodium lignosulfonate grafted acrylamide copolymer, 10-20 parts nano-sized biochar, 5-10 parts chitosan quaternary ammonium salt, and 1-3 parts compound enzyme preparation.

[0027] Preferably, the components in the specified mass fractions are: 50-60 parts cationic modified starch, 25-30 parts sodium lignosulfonate grafted acrylamide copolymer, 15-20 parts nano-sized biochar, 8-10 parts chitosan quaternary ammonium salt, and 2-3 parts compound enzyme preparation.

[0028] More preferably, the components in the specified mass fractions are: 50 parts cationic modified starch, 25 parts sodium lignosulfonate grafted acrylamide copolymer, 15 parts nano-sized biochar, 8 parts chitosan quaternary ammonium salt, and 2 parts compound enzyme preparation.

[0029] Specifically, the degree of substitution of the cationic modified starch is 0.3-0.5; and the molecular weight of the sodium lignosulfonate-grafted acrylamide copolymer is 8-12 million.

[0030] The cationic modified starch in this invention has the following functions: The 3-chloro-2-hydroxypropyltrimethylammonium chloride group introduced into cationic modified starch can form a molecular structure with a high positive charge density (degree of substitution 0.3-0.5), which can quickly neutralize the negative charge on the surface of sludge colloidal particles (mainly from microbial extracellular polymers, organic matter, etc.), significantly reducing the electrostatic repulsion between sludge particles, destroying colloidal stability, and laying the foundation for subsequent floc formation.

[0031] Cationic modified starch retains the long-chain structure of starch molecules. While neutralizing the charge, its linear molecular chains can adsorb multiple neutralized fine sludge particles through van der Waals forces, hydrogen bonds, and other interactions, connecting the dispersed particles into preliminary flocs. This synergistic effect of "charge neutralization-adsorption bridging" effectively solves the problem of small and easily broken flocs caused by single charge neutralizers (such as PAC), providing a stable "floc core" for further bridging by sodium lignosulfonate-grafted acrylamide copolymer.

[0032] The natural rigidity of starch molecular chains and the cationic groups introduced after modification together endow the flocs with good mechanical strength. During the pressure filtration dewatering process, the flocs formed by cationic modified starch are not easily broken by pressure, can maintain a stable structural morphology, avoid fine particles clogging the filter cloth, thereby improving dewatering efficiency and reducing the moisture content of the filter cake.

[0033] The hydroxyl groups in the cationic modified starch molecules can form hydrogen bonds with the amino groups of chitosan quaternary ammonium salt, constructing a preliminary network structure in the low-temperature premixing stage, providing a carrier for the uniform dispersion of nano-biochar and lignin graft copolymer; at the same time, its organic framework can generate interfacial interactions with the surface functional groups of nano-biochar, promoting the adsorption and transfer of water by the porous structure, and further enhancing the dehydration performance.

[0034] As a natural polymer derivative, cationic modified starch has good biocompatibility and biodegradability, and contains no inorganic metal components. Unlike PAC, its introduction does not increase ash content in sludge. Instead, through its own organic matter characteristics, it synergistically retains the original organic matter in the sludge, reducing dilution of the sludge's calorific value and providing favorable conditions for subsequent resource utilization such as incineration power generation.

[0035] The sodium lignosulfonate-grafted acrylamide copolymer in this invention has the following effects: It can enhance adsorption bridging capacity and promote floc growth: Sodium lignin sulfonate grafted with acrylamide copolymer combines the polycyclic aromatic structure of lignin with the long-chain linear structure of acrylamide. After oxidative pre-activation, the aldehyde and carboxyl active sites introduced form synergistic adsorption centers with the amide groups of the acrylamide segments, which can simultaneously bind multiple fine sludge particles whose charges have been initially neutralized by cationic modified starch. Its high molecular weight characteristics endow the molecular chains with sufficient length and flexibility, enabling them to connect dispersed floc "cores" across large spatial distances, entangle and aggregate small flocs into structurally stable large flocs, solving the problem of small flocs and easy loss in traditional PAC conditioning, and providing a larger solid-liquid separation unit for subsequent filter press dewatering.

[0036] It can enhance interfacial compatibility with other components and optimize system synergy: the hydrophilic groups (sulfonic acid groups, hydroxyl groups) of sodium lignosulfonate can form hydrogen bonds with the hydroxyl groups of cationic modified starch and generate electrostatic attraction with the amino groups of chitosan quaternary ammonium salt. During the mesophilic assembly stage, a continuous three-dimensional network structure is built through molecular chain entanglement, allowing the nano-biochar to be uniformly embedded within it. This interfacial bonding not only avoids the aggregation of nano-char, but also connects the porous adsorption function of nano-char with its own bridging function through the long chains of the copolymer, forming a synergistic pathway of "adsorption-convergence-aggregation", which accelerates the migration of sludge moisture to the filter cake surface.

[0037] It can improve floc toughness and shear resistance: The rigid aromatic ring structure of sodium lignin sulfonate and the flexible carbon chain of acrylamide segments form a "rigid-flexible" molecular skeleton, giving the resulting flocs both strength and elasticity. During stirring, mixing, and pressure filtration, this structure can resist shear and pressure damage, preventing filter cloth clogging caused by floc breakage, significantly reducing pressure filtration resistance, and improving dewatering efficiency. Compared to acrylamide polymers alone, the introduction of lignin segments improves floc toughness, making it more adaptable to the dynamic environment of industrial processing.

[0038] It can improve the resource utilization characteristics of sludge and reduce environmental risks: As a graft product of natural lignin derivative and acrylamide, this copolymer is a biodegradable organic polymer with no heavy metal or inorganic residues. Unlike PAC, its introduction does not increase sludge ash content; instead, it can increase the organic matter content of sludge through the carbon skeleton of lignin. Combined with the high calorific value of nano-biochar, it jointly promotes the increase of calorific value in conditioned sludge. Simultaneously, the sulfonic acid groups in its molecular structure can form complexes with potential heavy metal ions in the sludge, reducing the bioavailability of heavy metals and further broadening the resource utilization pathways of sludge (such as land application and incineration power generation).

[0039] In some embodiments of the present invention, the cationic modified starch is obtained by the following method: Starch was added to water to prepare a 25% concentration suspension, stirred at 30°C for 30 minutes, and cellulase and amylase were added at a mass ratio of 1:1, wherein the mass of cellulase and amylase was 0.5% of the mass of starch. After enzymatic hydrolysis for 30 minutes, the temperature was raised to 80°C for 10 minutes to inactivate the enzymes. The pH of the enzymatically hydrolyzed suspension was adjusted to 8.5 by adding 10% sodium hydroxide solution and stirring for 15 min. Then, 10% sodium hydroxide solution was added to adjust the pH to 11.0. 3-chloro-2-hydroxypropyltrimethylammonium chloride (CHPTAC) at 18% of the starch mass was added for ultrasonic-assisted modification. After the modification was completed, the mixture was subjected to gradient cooling and then centrifuged to collect the precipitate. The precipitate was washed three times with 70% ethanol solution. The washed precipitate was dried at -40°C and under a vacuum of 0.1 MPa and then pulverized to obtain the cationic modified starch.

[0040] Preferably, the ultrasonic-assisted modification temperature is 65°C, the ultrasonic power is 300W, the ultrasonic frequency is 20kHz, and the reaction time is 1.5 hours.

[0041] Preferably, the gradient cooling specifically involves lowering the temperature of the modified suspension to 40°C, holding it at that temperature for 30 minutes, and then lowering it to 25°C and holding it at that temperature for 30 minutes.

[0042] Specifically, when washing the precipitate three times with 70% ethanol solution: add the same mass of 70% ethanol solution as the starch to the precipitate, stir for 10 minutes, centrifuge at 3000 r / min for 10 minutes, collect the precipitate, and repeat the operation three times.

[0043] Understandably, the gradient preparation method (gradient alkalization-ultrasound-assisted) for preparing cationic modified starch has several advantages. First, gradient alkalization (adjusting the pH to 8.5±0.1 first and then increasing it to 11.0±0.1) avoids the problem of excessively high local alkali concentration caused by traditional one-time alkalization, reduces side reactions of excessive degradation of starch molecular chains, and gradually activates the active sites of starch hydroxyl groups, making the subsequent reaction of the cationic etherifying agent (CHPTAC) with the hydroxyl groups more uniform and reducing the distribution deviation of the final product's degree of substitution. Second, combined with intermittent ultrasound assistance, the ultrasonic cavitation effect can accelerate the diffusion rate of CHPTAC in the starch suspension, shorten the reaction time, and avoid starch gelatinization caused by sudden local temperature rises. In addition, the combination of gradient cooling and gradient ethanol washing can reduce the agglomeration of modified starch during purification, improve the fineness of the finished product, and ultimately improve the charge neutralization efficiency of the cationic modified starch, laying the foundation for efficient interaction with sludge colloidal particles and synergistic bridging with other components, while reducing energy consumption and raw material loss in industrial production.

[0044] In some embodiments of the present invention, the sodium lignosulfonate-grafted acrylamide copolymer is obtained by the following method: Sodium lignosulfonate was dissolved in water to prepare an 8% (w / w) sodium lignosulfonate solution. 5% (w / w) of a 30% (w / w) hydrogen peroxide solution was added to the sodium lignosulfonate solution. After stirring at 50°C for 60 minutes, 30% (w / w) of acrylamide monomer and 0.2% (w / w) of sodium persulfate were added. The reaction was carried out under nitrogen protection at 45°C for 1 hour. After the reaction was completed, the temperature was raised to 60°C, and 0.3% (w / w) of sodium bisulfite was added to continue the reaction for 2 hours to obtain a polymer. The polymer was then post-treated to obtain the sodium lignosulfonate-grafted acrylamide copolymer.

[0045] Preferably, the post-processing specifically includes: The polymer was dialyzed with water as the dialysate for 48 hours, with the dialysate being changed every 8 hours. After the dialysate was dialyzed, the polymer was dried at -45°C and a vacuum of 0.1 MPa for 24 hours.

[0046] Specifically, during dialysis: the polymer is transferred to a dialysis bag (molecular weight cutoff 100,000 Da), and dialyzed with deionized water for 48 hours, with the deionized water being changed every 8 hours.

[0047] Understandably, this invention employs an oxidative pre-activation + segmented initiation activation-grafting process to prepare sodium lignosulfonate-grafted acrylamide copolymer. Firstly, the oxidative pre-activation stage (treatment with 5% lignin by weight of 30% hydrogen peroxide at 50°C) precisely introduces active sites such as aldehyde and carboxyl groups onto the sodium lignosulfonate molecular chain, increasing the number of grafting reaction sites and solving the problem of insufficient grafting rate due to low lignin activity in traditional processes, ultimately improving the grafting rate. Secondly, the segmented initiation process uses a two-step control of "low molecular weight prepolymerization - high molecular weight growth." In the first stage, 0.2% ammonium persulfate is used at 45°C to initiate the formation of a prepolymer with a molecular weight of 3-5 million, laying a uniform framework for subsequent chain growth. In the second stage, the temperature is raised to 60°C and 0.3% sodium bisulfite (Redox) is added. The initiator promotes the further growth of molecular chains to 8-10 million, forming a gradient molecular structure of "low molecular weight segment anchoring - high molecular weight segment bridging". This ensures both the adsorption affinity between the copolymer and sludge particles and enhances the adsorption bridging ability. In addition, this process can reduce the formation of acrylamide homopolymer (through directional grafting of active sites). After dialysis purification, the content of small molecule impurities is reduced, so that the copolymer can not only synergistically achieve efficient charge neutralization and floc construction with cationic modified starch in subsequent sludge conditioning, but also improve floc toughness with rigid lignin segments, avoiding floc breakage during filter press. At the same time, since there are no excess small molecule impurities, it will not have a negative impact on the subsequent resource utilization of sludge (such as incineration calorific value). It comprehensively takes into account the copolymer preparation efficiency, structural performance and environmental compatibility.

[0048] In some embodiments of the present invention, the nanoscale biochar is obtained by the following methods: After crushing rice husks, they were mixed with water at a mass ratio of 1:10. Phosphoric acid at a mass of 3% of the rice husks was added, and the mixture was subjected to a hydrothermal reaction at 180°C for 2 hours to obtain a carbon-rich precursor. The carbon-rich precursor was heated to 300°C at a rate of 5°C / min under a nitrogen atmosphere and held at that temperature for 1 hour. Then, it was heated to 550°C at a rate of 5°C / min while water vapor was continuously introduced at a flow rate of 0.5 L / h and held at that temperature for 1.5 hours. After that, it was naturally cooled to 100°C and then removed. It was then pulverized at a pulverizing pressure of 0.8 MPa and a rotation speed of 10,000 r / min to obtain the nanoscale biochar.

[0049] Understandably, this invention employs a two-step method of hydrothermal carbonization-pyrolysis coupling + in-situ activation to prepare nanoscale biochar. First, the hydrothermal pretreatment stage (treating rice husks with 3% phosphoric acid at 180±2℃ and 1.0-1.2MPa) partially hydrolyzes and carbonizes the cellulose and hemicellulose in the rice husks, forming carbon-rich precursors. This not only avoids excessive shrinkage and carbon loss caused by direct pyrolysis but also pre-constructs preliminary pores through the catalytic effect of phosphoric acid, laying the foundation for subsequent activation. Second, the gradient pyrolysis-in-situ activation coupling process first removes volatile organic compounds by holding at 300℃ for 1 hour to prevent low-boiling-point impurities from affecting pore development. Then, the temperature is raised to 550℃ and steam is introduced for in-situ activation, where the steam reacts with the carbon material through oxidation. This method allows for precise control of pore type and distribution, increasing the specific surface area of ​​biochar and significantly enhancing its adsorption and water-locking capacity for sludge. Furthermore, the two-step process reduces the mechanical strength of rice husks through hydrothermal pretreatment, making it easier to obtain uniformly sized nano-particles during subsequent airflow pulverization. This solves the problems of uneven particle size and severe agglomeration in traditional biochar, ultimately enabling the nano-biochar to be uniformly dispersed in the conditioner system and to construct drainage channels through its porous structure. This synergistic effect with other organic components improves sludge dewatering efficiency. Simultaneously, the high calorific value of rice husk-based char further enhances the calorific value of the conditioned sludge, providing strong support for sludge resource utilization. Moreover, the entire process generates no harmful waste, meeting the requirements of green and environmentally friendly industrial production.

[0050] In some embodiments of the present invention, the compound enzyme preparation is composed of 50% cellulase, 30% protease and 20% lipase, and the enzyme activity in the compound enzyme preparation is ≥1000U / g.

[0051] Understandably, the complex enzyme preparation composed of cellulase (50%), protease (30%), and lipase (20%) plays a key role in "targeted cell wall disruption and synergistic degradation" in organic sludge conditioners, laying an efficient foundation for subsequent physicochemical conditioning: cellulase can specifically degrade the cellulose polysaccharide skeleton of extracellular polymeric substances (EPS) in sludge colloids, destroy the three-dimensional network structure formed by EPS, and release the encapsulated free and bound water; protease can hydrolyze the protein components in EPS, break the peptide bonds between protein molecules, reduce the viscosity of sludge, and improve sludge flowability; lipase can decompose oily substances in sludge, prevent oil from forming a hydrophobic film on the surface of sludge particles that hinders water removal, and at the same time reduce the interference of oil on the adsorption and bridging effect of subsequent polymeric conditioners. The three enzyme preparations work synergistically in proportion to not only break down the stable structure of sludge colloids at multiple component levels, allowing for more full exposure of negative charges on the surface of sludge particles and improving the charge neutralization efficiency of components such as cationic modified starch, but also reduce the occupation of ineffective volume in sludge by degrading some recalcitrant organic matter. Combined with the adsorption and drainage channel construction of nano-biochar, the moisture content of sludge after pressure filtration is further reduced. At the same time, since the enzymatic hydrolysis products are small-molecule organic matter, they can be synergistically retained with the original organic matter in the sludge, avoiding dilution of the calorific value of the sludge and providing a guarantee for subsequent resource utilization.

[0052] This invention also provides a method for preparing the organic sludge conditioner described in the above technical solution, comprising the following steps: The cationic modified starch was mixed with chitosan quaternary ammonium salt and stirred at 30°C and 400 r / min for 10 minutes. Then the lignin graft copolymer was added, the temperature was raised to 50°C, the stirring speed was reduced to 200 r / min, and the mixture was stirred for 20 minutes. Then the nano-biochar was added, the temperature was raised to 60°C, and the mixture was stirred at 200 r / min for 15 minutes. Finally, the temperature was lowered to 25°C, the compound enzyme preparation was added, and the mixture was stirred at 100 r / min for 5 minutes to obtain the organic sludge conditioner.

[0053] Understandably, this invention employs a temperature-responsive mixing process to prepare an organic sludge conditioner. The low-temperature premixing stage (30°C) promotes the formation of stable hydrogen bonds between the hydroxyl groups of cationic modified starch and the amino groups of chitosan quaternary ammonium salt, constructing a uniform preliminary network structure and avoiding the disordered binding caused by excessive molecular chain movement at high temperatures. The medium-temperature assembly stage (50°C) enhances the flexibility of the lignin-grafted copolymer molecular chains through moderate heating, making it easier for them to form chain segment entanglements with the preliminary network structure. Simultaneously, hydrophobic interactions improve the compatibility of each polymer component, reducing interfacial separation. The high-temperature activation stage (60°C) further increases molecular kinetic energy, promoting strong interfacial bonding between the functional groups on the surface of the nano-biomass char and the polymer network, solving the problem of easy agglomeration of nanoparticles and achieving uniform dispersion. The low-temperature curing stage (25°C) fixes the formed three-dimensional assembly structure through cooling, while avoiding the destruction of the composite enzyme activity by high temperatures. This invention achieves the transformation of each component from "physical mixing" to "molecular-level synergy" simply by changing the temperature gradient, enabling the conditioner to form a stable "charge neutralization-adsorption bridging-pore adsorption" functional network. This not only improves the overall conditioning effect of the conditioner on sludge but also extends storage stability, while ensuring the simplicity and economy of industrial production.

[0054] The water used in this invention is preferably deionized water.

[0055] In this invention: the starch is corn starch; the purity of 3-chloro-2-hydroxypropyltrimethylammonium chloride (CHPTAC) is ≥98%, and the effective chlorine content is ≥30%; the molecular weight of sodium sulfonate is 5000-8000, and the degree of sulfonation is ≥60%; the degree of deacetylation of chitosan quaternary ammonium salt is ≥85%, the degree of quaternization substitution is ≥0.6, and the viscosity is 100-300 mPa·s (2% mass concentration aqueous solution, 25℃).

[0056] The present invention also provides an application of the organic sludge conditioner described in the above technical solution in the conditioning of sludge.

[0057] Specifically, this invention can also be applied to the treatment of silicon-containing wastewater during silicon processing. It can improve sludge characteristics, remove some oil from wastewater under slightly acidic conditions, prevent filter cloth clogging, and improve the quality of recycled water.

[0058] Example 1 I. Components of Organic Sludge Conditioner 40 parts cationic modified starch, 20 parts sodium lignosulfonate grafted acrylamide copolymer, 10 parts nano-sized biochar, 5 parts chitosan quaternary ammonium salt and 1 part compound enzyme preparation.

[0059] II. Preparation of each component: Cationic modified starch: Corn starch is added to deionized water to prepare a 25% concentration suspension, stirred at 30°C for 30 minutes, and cellulase and amylase are added at a mass ratio of 1:1, wherein the mass of cellulase and amylase is 0.5% of the starch mass. After enzymatic hydrolysis for 30 minutes, the temperature is raised to 80°C for 10 minutes to inactivate the enzyme. The pH of the enzymatically hydrolyzed suspension was adjusted to 8.5 by adding 10% sodium hydroxide solution and stirring for 15 min. Then, 10% sodium hydroxide solution was added to adjust the pH to 11.0. 3-chloro-2-hydroxypropyltrimethylammonium chloride (18% by weight of starch) was added for ultrasonic-assisted modification. After the modification was completed, the suspension was subjected to gradient cooling and then centrifuged to collect the precipitate. 70% ethanol solution (equal to the weight of starch) was added to the precipitate and stirred for 10 min. The precipitate was then centrifuged at 3000 r / min for 10 min and collected. The washing process was repeated 3 times. The washed precipitate was dried at -40℃ and 0.1 MPa vacuum and then pulverized to obtain the cationic modified starch.

[0060] Sodium lignosulfonate-grafted acrylamide copolymer: Sodium lignosulfonate was dissolved in deionized water to prepare an 8% (w / w) sodium lignosulfonate solution. 5% (w / w) of a 30% (w / w) hydrogen peroxide solution was added to the sodium lignosulfonate solution. After stirring at 50°C for 60 minutes, 30% (w / w) of acrylamide monomer and 0.2% (w / w) of sodium persulfate were added. The reaction was carried out under nitrogen protection at 45°C for 1 hour. After the reaction, the temperature was raised to 60°C, and 0.3% (w / w) of sodium bisulfite was added, and the reaction continued for another 2 hours to obtain the polymer. The polymer was dialyzed using deionized water as the dialysate for 48 hours, with the dialysate being changed every 8 hours. After the reaction, the dialyzed polymer was dried at -45°C and a vacuum of 0.1 MPa for 24 hours to obtain the sodium lignosulfonate-grafted acrylamide copolymer.

[0061] Nanoscale biochar: Rice husks are crushed and mixed with water at a mass ratio of 1:10. Phosphoric acid at 3% of the mass of rice husks is added and the mixture is hydrothermally reacted at 180°C for 2 hours to obtain a carbon-rich precursor. The carbon-rich precursor was heated to 300°C at a rate of 5°C / min under a nitrogen atmosphere and held at that temperature for 1 hour. Then, it was heated to 550°C at a rate of 5°C / min while water vapor was continuously introduced at a flow rate of 0.5 L / h and held at that temperature for 1.5 hours. After that, it was naturally cooled to 100°C and then removed. It was then pulverized at a pulverizing pressure of 0.8 MPa and a rotation speed of 10,000 r / min to obtain the nanoscale biochar.

[0062] The compound enzyme preparation consists of 50% cellulase, 30% protease and 20% lipase.

[0063] III. Preparation Method of Organic Sludge Conditioner 40 parts of cationic modified starch and 5 parts of chitosan quaternary ammonium salt were mixed and stirred at 30°C and 400 r / min for 10 minutes. Then, 20 parts of lignin graft copolymer were added, the temperature was raised to 50°C, the stirring speed was reduced to 200 r / min, and the mixture was stirred for 20 minutes. Then, 10 parts of nano-biochar were added, the temperature was raised to 60°C, and the mixture was stirred at 200 r / min for 15 minutes. Finally, the temperature was lowered to 25°C, 1 part of compound enzyme preparation was added, and the mixture was stirred at 100 r / min for 5 minutes to obtain the organic sludge conditioner.

[0064] Example 2 I. Components of Organic Sludge Conditioner 50 parts cationic modified starch, 25 parts sodium lignosulfonate grafted acrylamide copolymer, 15 parts nano-sized biochar, 8 parts chitosan quaternary ammonium salt, and 2 parts compound enzyme preparation II. Preparation of each component: Cationic modified starch: Corn starch is added to deionized water to prepare a 25% concentration suspension, stirred at 30°C for 30 minutes, and cellulase and amylase are added at a mass ratio of 1:1, wherein the mass of cellulase and amylase is 0.5% of the starch mass. After enzymatic hydrolysis for 30 minutes, the temperature is raised to 80°C for 10 minutes to inactivate the enzyme. The pH of the enzymatically hydrolyzed suspension was adjusted to 8.5 by adding 10% sodium hydroxide solution and stirring for 15 min. Then, 10% sodium hydroxide solution was added to adjust the pH to 11.0. 3-chloro-2-hydroxypropyltrimethylammonium chloride (18% by weight of starch) was added for ultrasonic-assisted modification. After the modification was completed, the suspension was subjected to gradient cooling and then centrifuged to collect the precipitate. 70% ethanol solution (equal to the weight of starch) was added to the precipitate and stirred for 10 min. The precipitate was then centrifuged at 3000 r / min for 10 min and collected. The washing process was repeated 3 times. The washed precipitate was dried at -40℃ and 0.1 MPa vacuum and then pulverized to obtain the cationic modified starch.

[0065] Sodium lignosulfonate-grafted acrylamide copolymer: Sodium lignosulfonate was dissolved in deionized water to prepare an 8% (w / w) sodium lignosulfonate solution. 5% (w / w) of a 30% (w / w) hydrogen peroxide solution was added to the sodium lignosulfonate solution. After stirring at 50°C for 60 minutes, 30% (w / w) of acrylamide monomer and 0.2% (w / w) of sodium persulfate were added. The reaction was carried out under nitrogen protection at 45°C for 1 hour. After the reaction, the temperature was raised to 60°C, and 0.3% (w / w) of sodium bisulfite was added, and the reaction continued for another 2 hours to obtain the polymer. The polymer was dialyzed using deionized water as the dialysate for 48 hours, with the dialysate being changed every 8 hours. After the reaction, the dialyzed polymer was dried at -45°C and a vacuum of 0.1 MPa for 24 hours to obtain the sodium lignosulfonate-grafted acrylamide copolymer.

[0066] Nanoscale biochar: Rice husks are crushed and mixed with water at a mass ratio of 1:10. Phosphoric acid at 3% of the mass of rice husks is added and the mixture is hydrothermally reacted at 180°C for 2 hours to obtain a carbon-rich precursor. The carbon-rich precursor was heated to 300°C at a rate of 5°C / min under a nitrogen atmosphere and held at that temperature for 1 hour. Then, it was heated to 550°C at a rate of 5°C / min while water vapor was continuously introduced at a flow rate of 0.5 L / h and held at that temperature for 1.5 hours. After that, it was naturally cooled to 100°C and then removed. It was then pulverized at a pulverizing pressure of 0.8 MPa and a rotation speed of 10,000 r / min to obtain the nanoscale biochar.

[0067] The compound enzyme preparation consists of 50% cellulase, 30% protease and 20% lipase.

[0068] III. Preparation Method of Organic Sludge Conditioner 50 parts of cationic modified starch and 8 parts of chitosan quaternary ammonium salt were mixed and stirred at 30°C and 400 r / min for 10 minutes. Then, 25 parts of lignin graft copolymer were added, the temperature was raised to 50°C, the stirring speed was reduced to 200 r / min, and the mixture was stirred for 20 minutes. Then, 15 parts of nano-biochar were added, the temperature was raised to 60°C, and the mixture was stirred at 200 r / min for 15 minutes. Finally, the temperature was lowered to 25°C, 2 parts of compound enzyme preparation were added, and the mixture was stirred at 100 r / min for 5 minutes to obtain the organic sludge conditioner.

[0069] Example 3 I. Components of Organic Sludge Conditioner The mixture consisted of 60 parts cationic modified starch, 30 parts sodium lignosulfonate grafted acrylamide copolymer, 20 parts nano-sized biochar, 10 parts chitosan quaternary ammonium salt, and 3 parts compound enzyme preparation.

[0070] II. Preparation of each component: Cationic modified starch: Corn starch is added to deionized water to prepare a 25% concentration suspension, stirred at 30°C for 30 minutes, and cellulase and amylase are added at a mass ratio of 1:1, wherein the mass of cellulase and amylase is 0.5% of the starch mass. After enzymatic hydrolysis for 30 minutes, the temperature is raised to 80°C for 10 minutes to inactivate the enzyme. The pH of the enzymatically hydrolyzed suspension was adjusted to 8.5 by adding 10% sodium hydroxide solution and stirring for 15 min. Then, 10% sodium hydroxide solution was added to adjust the pH to 11.0. 3-chloro-2-hydroxypropyltrimethylammonium chloride (18% by weight of starch) was added for ultrasonic-assisted modification. After the modification was completed, the suspension was subjected to gradient cooling and then centrifuged to collect the precipitate. 70% ethanol solution (equal to the weight of starch) was added to the precipitate and stirred for 10 min. The precipitate was then centrifuged at 3000 r / min for 10 min and collected. The washing process was repeated 3 times. The washed precipitate was dried at -40℃ and 0.1 MPa vacuum and then pulverized to obtain the cationic modified starch.

[0071] Sodium lignosulfonate-grafted acrylamide copolymer: Sodium lignosulfonate was dissolved in deionized water to prepare an 8% (w / w) sodium lignosulfonate solution. 5% (w / w) of a 30% (w / w) hydrogen peroxide solution was added to the sodium lignosulfonate solution. After stirring at 50°C for 60 minutes, 30% (w / w) of acrylamide monomer and 0.2% (w / w) of sodium persulfate were added. The reaction was carried out under nitrogen protection at 45°C for 1 hour. After the reaction, the temperature was raised to 60°C, and 0.3% (w / w) of sodium bisulfite was added, and the reaction continued for another 2 hours to obtain the polymer. The polymer was dialyzed using deionized water as the dialysate for 48 hours, with the dialysate being changed every 8 hours. After the reaction, the dialyzed polymer was dried at -45°C and a vacuum of 0.1 MPa for 24 hours to obtain the sodium lignosulfonate-grafted acrylamide copolymer.

[0072] Nanoscale biochar: Rice husks are crushed and mixed with water at a mass ratio of 1:10. Phosphoric acid at 3% of the mass of rice husks is added and the mixture is hydrothermally reacted at 180°C for 2 hours to obtain a carbon-rich precursor. The carbon-rich precursor was heated to 300°C at a rate of 5°C / min under a nitrogen atmosphere and held at that temperature for 1 hour. Then, it was heated to 550°C at a rate of 5°C / min while water vapor was continuously introduced at a flow rate of 0.5 L / h and held at that temperature for 1.5 hours. After that, it was naturally cooled to 100°C and then removed. It was then pulverized at a pulverizing pressure of 0.8 MPa and a rotation speed of 10,000 r / min to obtain the nanoscale biochar.

[0073] The compound enzyme preparation consists of 50% cellulase, 30% protease and 20% lipase.

[0074] III. Preparation Method of Organic Sludge Conditioner 60 parts of cationic modified starch and 10 parts of chitosan quaternary ammonium salt were mixed and stirred at 30°C and 400 r / min for 10 minutes. Then, 30 parts of lignin graft copolymer were added, the temperature was raised to 50°C, the stirring speed was reduced to 200 r / min, and the mixture was stirred for 20 minutes. Then, 20 parts of nano-biochar were added, the temperature was raised to 60°C, and the mixture was stirred at 200 r / min for 15 minutes. Finally, the temperature was lowered to 25°C, 3 parts of compound enzyme preparation were added, and the mixture was stirred at 100 r / min for 5 minutes to obtain the organic sludge conditioner.

[0075] Application Example 1 The organic sludge conditioner prepared in Example 2 was added to the silicon-containing wastewater during the silicon processing at a rate of 0.1 g / L.

[0076] Effect test 1. Test Sample Sludge sample: Excess sludge from municipal wastewater treatment plant (typical organic sludge) was selected. Its basic properties are as follows: water content 98.2%, dry matter content 1.8% (i.e., 1 kg of sludge contains 18 g of dry sludge), initial calorific value 15.3 MJ / kg (dry sludge basis), pH=7.2, viscosity 320 mPa·s (25℃).

[0077] 2. Experimental reagents Experimental group: Organic sludge conditioner prepared in Example 2 of this invention Control group: Traditional industrial grade PAC (polyaluminum chloride, Al2O3 content ≥30%, basicity 60%-80%, powder).

[0078] Each experiment was repeated three times, and the average value was taken as the final data to ensure the reliability of the results.

[0079] 3. Testing equipment Equipment: Six-unit agitator (controllable speed 0-300r / min, model JJ-4), frame filter press (filtration area 0.1m²) 2 The equipment includes: a working pressure of 0.6MPa (model XAMY-10 / 630), an infrared moisture analyzer (testing accuracy ±0.01%, model MA150), an oxygen bomb calorimeter (testing accuracy ±0.1MJ / kg, model ZDHW-5000), and an electronic balance (weighing range 0-10kg, accuracy 0.1g, model JA10002).

[0080] 4. Test Procedure (1) Comparison test of effective dosage: Take 10 kg of sludge sample (180 g of dry sludge) and divide it into 6 groups, each group containing 1.67 kg (30 g of dry sludge). The experimental group set up three dosage gradients: 0.15% (0.045g), 0.3% (0.09g), and 0.6% (0.18g) of the sludge dry weight. The conditioner was prepared into a solution at a ratio of 1:20 and then added to the sludge. The solution was stirred at 200r / min for 1min and then at 50r / min for 3min. The control group had three dosage gradients: 2% (0.6g), 4% (1.2g), and 8% (2.4g) of the sludge dry weight. PAC was prepared into a solution at a ratio of 1:10 and then added to the sludge. The stirring method was the same as that of the experimental group. All sludge samples were filtered using a plate and frame filter press at a pressure of 0.6 MPa for 30 minutes, and the moisture content of the sludge after filtration was measured. Using "moisture content ≤ 80%" as the effective conditioning standard, the minimum effective dosage of the two groups of agents was determined, and the results are shown in Table 1.

[0081] Table 1. Results of the Comparison Test on Effective Dosage

[0082] It is evident that the minimum effective dosage of organic sludge conditioner is 0.15% (dry weight percentage of sludge), while the minimum effective dosage of traditional PAC is 4% (dry weight percentage of sludge), with a ratio of 1:26.7. Furthermore, the moisture content of organic sludge conditioner drops to 71.5% at a dosage of 0.15%, which is superior to the effect of PAC at 8%. Comparing the effective dosage ranges: organic sludge conditioner is 0.15%-0.6%, while traditional PAC is 4%-8%, meaning the former's dosage is only 1 / 13.3 (0.6% / 8%) to 1 / 11.1 (0.15% / 4%) of the latter. (2) Comparative test on the effect of sludge reduction: Take 10 kg of sludge sample (180 g of dry sludge) and divide it into 2 groups, each group containing 5 kg (90 g of dry sludge). The experimental group was given the organic conditioner at the minimum effective dosage (0.15%), and the control group was given PAC at the minimum effective dosage (4%). The stirring and filtration operations were the same as before. Two sets of sludge cakes after filter pressing were collected, and the moisture content was measured using an infrared moisture analyzer. The amount of oven-dry sludge was calculated (Oven-dry amount = Total mass of sludge cake × (1 - Moisture content)). The "additional solids introduced by the reagent" was defined as "absolutely dry sludge volume - initial dry sludge volume". The sludge volume reduction ratio was calculated as "(absolutely dry sludge volume of PAC group - absolutely dry sludge volume of organic group) / absolutely dry sludge volume of PAC group × 100%". The results are shown in Table 2.

[0083] Table 2 Comparison of sludge reduction effects

[0084] As can be seen, the amount of oven-dried sludge in the experimental group (Example 2) was 91.0g, only 1.0g more than the initial amount of dry sludge (this was the oven-dried amount of the reagent itself, without any additional inorganic impurities); the amount of oven-dried sludge in the control group (traditional PAC group) was 100.3g, 10.3g more than the initial amount of dry sludge (including inorganic residues such as Al(OH)3 generated by PAC hydrolysis); and according to the sludge reduction ratio, (100.3-91.0) / 100.3×100% The reduction rate is approximately 9.3%. If we compare the organic sludge conditioner dosage of 0.6% (dry weight 90 + 0.54 = 90.54 g) with the PAC dosage of 8% (dry weight 90 + 21.6 = 111.6 g), the reduction rate is (111.6 - 90.54) / 111.6 × 100% ≈ 18.8%. Considering different dosage gradients, the organic sludge conditioner of this application reduces sludge volume by 13%-17% compared to traditional PAC.

[0085] (3) Comparison test of sludge calorific value: Take 10 kg of sludge sample (180 g of dry sludge, initial calorific value 15.3 MJ / kg), divide it into 2 groups, each group 5 kg (90 g of dry sludge). The experimental group was given organic conditioner at a dosage of 0.3% (as a percentage of sludge dry weight), while the control group was given PAC at a dosage of 4%. The stirring and filtration operations were the same as before. Two sets of sludge cakes after filter pressing were collected, dried in an oven at 105℃ for 24 hours until constant weight, pulverized and passed through a 100-mesh sieve to prepare dry sludge samples; The calorific value (dry basis) of the two groups of dry mud samples was determined using an oxygen bomb calorimeter, and the increase in calorific value was calculated. The results are shown in Table 3.

[0086] Table 3 Comparison of Sludge Calorific Value Test Results

[0087] As can be seen, the calorific value of the sludge after conditioning according to the present invention increased to 20.8 MJ / kg, an increase of 35.9% compared to the initial calorific value; while the calorific value after conditioning with traditional PAC decreased to 12.1 MJ / kg, a decrease of 20.9% compared to the initial calorific value, showing a significant difference between the two. The components of the present invention (cationically modified starch, lignin graft copolymer, and nano-biochar) are all high-calorific-value organic / carbon-based materials (the calorific value of nano-biochar itself is ≥25 MJ / kg), and there is no inorganic impurity dilution. At the same time, the compound enzyme preparation only degrades low-calorific-value small-molecule organic matter (such as some polysaccharides) and does not affect the calorific value contribution of the core organic matter; while the inorganic aluminum salts (ash) introduced by PAC directly dilute the concentration of organic matter, resulting in a significant decrease in calorific value. The calorific value of the sludge after conditioning according to this invention (20.8 MJ / kg) is close to that of lignite (16-25 MJ / kg), and it can be directly used for incineration power generation. However, the sludge after PAC conditioning has too low a calorific value (<15 MJ / kg), and it needs to be blended with coal to meet the incineration requirements, which increases the cost of resource recovery.

[0088] (4) Experiment on the treatment of silicon-containing wastewater Silicon-containing wastewater sample: taken from wastewater of silicon wafer cutting production line, with the following characteristics: pH=5.2 (slightly acidic), silicon content 3.8g / L, oil concentration 126mg / L, turbidity 185NTU, COD=320mg / L.

[0089] Experimental grouping Experimental group: Added organic sludge conditioner (concentration 0.1g / L); Control group 1: Added conventional PAC (concentration 3g / L) Control group 2: Blank treatment (no drugs were added).

[0090] Experimental procedure: Take 1L of silicon-containing wastewater sample for each group, adjust the pH to 5.5 (slightly acidic conditions); add the reagent according to the ratio, stir at 200r / min for 2min, stir at 50r / min for 5min; let stand for 10min and then filter (using 0.45μm filter cloth), and measure various indicators as shown in Table 4.

[0091] Table 4. Experimental Results of Silicon-Containing Wastewater Treatment

[0092] It can be seen that the sludge moisture content of the experimental group was reduced by 11.2% and the specific resistance was reduced by 47.5% compared with the PAC group. This is because the floc structure formed by the conditioner is more compact and the dewatering performance is better.

[0093] Under slightly acidic conditions, the composite enzyme preparation and lignin graft copolymer in this invention work synergistically to achieve an oil removal rate 2.1 times that of the PAC group, effectively reducing oil adhesion to the filter cloth.

[0094] The filtration time of the experimental group was only 53.8% of that of the PAC group, and the degree of pollution on the filter cloth surface was significantly reduced; the turbidity and COD of the recycled water were reduced by 43.4% and 35.6% respectively, due to the stronger adsorption effect of nano-biochar and the stronger retention capacity of polymer flocs.

[0095] The cationic modified starch in this invention exhibits a charge adsorption effect with silicon particles, resulting in a silicon removal rate that is slightly higher than that of PAC, thereby enhancing the recycling value of reclaimed water.

[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the protection scope of the claims of the present invention.

Claims

1. An organic sludge conditioner, characterized in that, The components include the following parts by mass: 40-60 parts cationic modified starch, 20-30 parts sodium lignosulfonate grafted acrylamide copolymer, 10-20 parts nano-sized biochar, 5-10 parts chitosan quaternary ammonium salt and 1-3 parts compound enzyme preparation. The cationic modified starch is obtained by the following method: Starch was added to water to prepare a 25% concentration suspension, stirred at 30°C for 30 minutes, and cellulase and amylase were added at a mass ratio of 1:1, wherein the mass of cellulase and amylase was 0.5% of the mass of starch. After enzymatic hydrolysis for 30 minutes, the temperature was raised to 80°C for 10 minutes to inactivate the enzymes. The pH of the enzymatically hydrolyzed suspension was adjusted to 8.5 by adding 10% sodium hydroxide solution and stirring for 15 min. Then, 10% sodium hydroxide solution was added to adjust the pH to 11.

0. 3-chloro-2-hydroxypropyltrimethylammonium chloride (18% by weight of starch) was added for ultrasonic-assisted modification. After the modification was completed, the mixture was subjected to gradient cooling and then centrifuged to collect the precipitate. The precipitate was washed three times with 70% ethanol solution. The washed precipitate was dried at -40°C and under a vacuum of 0.1 MPa and then pulverized to obtain the cationic modified starch. The ultrasonic-assisted modification temperature was 65℃, the ultrasonic power was 300W, the ultrasonic frequency was 20kHz, and the reaction time was 1.5 hours. The gradient cooling process specifically involves lowering the temperature of the modified suspension to 40°C, holding it at that temperature for 30 minutes, and then lowering it to 25°C and holding it at that temperature for 30 minutes. The sodium lignosulfonate-grafted acrylamide copolymer was obtained by the following method: Sodium lignin sulfonate was dissolved in water to prepare an 8% (w / w) sodium lignin sulfonate solution. 5% (w / w) of a 30% (w / w) hydrogen peroxide solution was added to this solution. After stirring at 50°C for 60 minutes, 30% (w / w) of acrylamide monomer and 0.2% (w / w) of sodium persulfate were added. The reaction was carried out under nitrogen protection at 45°C for 1 hour. After the reaction, the temperature was raised to 60°C to allow for further reaction. The reaction was continued for 2 hours with 0.3% sodium bisulfite to obtain a polymer. The polymer was then post-treated to obtain the sodium lignosulfonate-grafted acrylamide copolymer. The post-processing specifically includes: The polymer was dialyzed with water as the dialysate for 48 hours, with the dialysate being changed every 8 hours. After the dialysate was dialyzed, the polymer was dried at -45°C and a vacuum of 0.1 MPa for 24 hours.

2. The organic sludge conditioner according to claim 1, characterized in that, The nanoscale biochar was obtained by the following method: After crushing rice husks, they were mixed with water at a mass ratio of 1:

10. Phosphoric acid at a mass of 3% of the rice husks was added, and the mixture was subjected to hydrothermal reaction at 180°C for 2 hours to obtain a carbon-rich precursor. The carbon-rich precursor was heated to 300°C at a rate of 5°C / min under a nitrogen atmosphere and held at that temperature for 1 hour. Then, it was heated to 550°C at a rate of 5°C / min while water vapor was continuously introduced at a flow rate of 0.5 L / h and held at that temperature for 1.5 hours. After that, it was naturally cooled to 100°C and then removed. It was then pulverized at a pulverizing pressure of 0.8 MPa and a rotation speed of 10,000 r / min to obtain the nanoscale biochar.

3. The organic sludge conditioner according to claim 1, characterized in that, The compound enzyme preparation consists of 50% cellulase, 30% protease and 20% lipase, and the enzyme activity in the compound enzyme preparation is ≥1000U / g.

4. A method for preparing an organic sludge conditioner as described in any one of claims 1-3, characterized in that, The preparation steps include the following: The cationic modified starch was mixed with chitosan quaternary ammonium salt and stirred at 30°C and 400 r / min for 10 minutes. Then, the sodium lignosulfonate grafted acrylamide copolymer was added, the temperature was raised to 50°C, the stirring speed was reduced to 200 r / min, and the mixture was stirred for 20 minutes. Then, the nano-scale biochar was added, the temperature was raised to 60°C, and the mixture was stirred at 200 r / min for 15 minutes. Finally, the temperature was lowered to 25°C, the compound enzyme preparation was added, and the mixture was stirred at 100 r / min for 5 minutes to obtain the organic sludge conditioner.

5. The application of an organic sludge conditioner in sludge conditioning, characterized in that, The organic sludge conditioner is the organic sludge conditioner as described in claim 1.

Citation Information

Patent Citations

  • Condition study on copolymerization and grafting of acrylamide and lignosulfonate

    CN104672404A

  • Recyclable mud-water separation material for sludge, and application thereof

    CN109179964A

  • Sludge conditioning agent and application thereof

    CN110372174A

  • Flocculation treatment of muddy water

    JP1996215686A